Research on tunnel ventilation systems: Dust Diffusion and Pollution Behaviour by air curtains based on CFD technology and field measurement - Liu, Qiang; Nie, Wen; Hua, Yun; Peng, Huitian; Liu, Changqi; Wei, Cunhou (Building and environment, 2019)
In order to further improve an air curtain's dust suppression performance in tunnels, this paper made an in-depth analysis of the effects of an air curtain generator's radial and axial pressure airflow rate and a dust removal fan's exhaust airflow rate on the diffusion and pollution behaviors of dust. Through CFD Technology and field measurements, it can be observed that: when the air curtain generator's axial-to-radial pressure airflow rate ratio (Ra/r) varied within the range of 1/9–6/4, the diffusion distance of high-concentration dust (with a concentration over 10 mg/m3) decreased with the decrease of Ra/r; and when Ra/r = 1/9, the formed airflow curtains exhibited the most favorable dust suppression performance. In addition: when the dust removal fan's exhaust-to-pressure airflow rate ratio (Re/p) increased, the diffusion distance of high-concentration dust decreased; and when Re/p = 1.2, the dust produced could be suppressed effectively by the air curtains. Finally, field measurements reveal that when a dust removal fan with a Re/p of 1.2 and an air curtain generator with a Ra/r of 1/9 were used in combination, high-concentration dust can be controlled fully within a range of 5.49 m from the head-on section by the formed air curtains, and the average dust concentration in the region 5–50 m away from the head-on section in tunnel was reduced to 9.82 mg/m3; i.e., the excavator driver and workers can be protected effectively. [Display omitted] •A physical model of 3down 905 tunnel was established.•Dust Diffusion and Pollution Behaviour were simulated using CFD Technology.•Dust Diffusion and Pollution Behaviour were verified through field measurements.•The optimal parameters of the Ra/r and Re/p were determined.